The lion inside - Bright, Rachel (New York : Scholastic, 2015)
You don't have to be big and brave to find your roar. Being little isn't always easy. But when Mouse sets off on a journey to find his roar, he discovers that even the smallest creature can have the heart of a lion.
Keywords: a -- a -- a